2020
DOI: 10.1038/s41467-020-15694-y
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic stress triggers the activation of IRE1α-dependent RNA decay to modulate the DNA damage response

Abstract: The molecular connections between homeostatic systems that maintain both genome integrity and proteostasis are poorly understood. Here we identify the selective activation of the unfolded protein response transducer IRE1α under genotoxic stress to modulate repair programs and sustain cell survival. DNA damage engages IRE1α signaling in the absence of an endoplasmic reticulum (ER) stress signature, leading to the exclusive activation of regulated IRE1α-dependent decay (RIDD) without activating its canonical out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 59 publications
(75 reference statements)
3
66
0
Order By: Relevance
“…In addition, our work indicates activation of the IRE-1/XBP-1 branch of the UPR ER upon DNA damage as a cellular maintenance program, whereas recent works suggest it might not be the case in proliferating cells. A study of mouse embryonic fibroblasts revealed that DNA damage engages regulated IRE1α-dependent decay (RIDD) to modulate DNA damage response genes, without activating XBP1 and canonical UPR genes (42). Moreover, DNA damage in cancer cell line HCT116 even suppresses IRE1α-XBP1 to stabilize pro-apoptotic protein BIK that contributes to apoptotic cell death (43), suggesting that DNA damage appears not to activate canonical UPR ER in proliferating cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our work indicates activation of the IRE-1/XBP-1 branch of the UPR ER upon DNA damage as a cellular maintenance program, whereas recent works suggest it might not be the case in proliferating cells. A study of mouse embryonic fibroblasts revealed that DNA damage engages regulated IRE1α-dependent decay (RIDD) to modulate DNA damage response genes, without activating XBP1 and canonical UPR genes (42). Moreover, DNA damage in cancer cell line HCT116 even suppresses IRE1α-XBP1 to stabilize pro-apoptotic protein BIK that contributes to apoptotic cell death (43), suggesting that DNA damage appears not to activate canonical UPR ER in proliferating cells.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, in mammals, known RIDD substrates seem to possess and require for cleavage an XBP1-like consensus loop sequence CNGCAGN, enclosed by a stable stem [40][41][42][43] . Besides ER load, mammalian RIDD regulates additional cellular functions, including triglyceride and cholesterol metabolism 44 ; apoptosis signaling through DR5 [45][46][47] ; protective autophagy via BLOC1S1 (BLOS1) 48 ; and DNA repair through Ruvbl1 49,50 . A canonical stem-loop endomotif is necessary but not sufficient to predict mammalian RIDD, while translational stalling can enhance mRNA depletion 41 .…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the UPR depends on the ER transmembrane proteins and sensors including inositol-requiring enzyme 1 (IRE1α), protein kinase R (PKR)-like endoplasmic reticulum kinase (PERK), activating transcription factor 6 (ATF6) and cyclic adenosine monophosphate (cAMP)-responsive element-binding protein H (CREBH) [ 27 , 28 , 29 , 30 ] ( Figure 1 ). Both PERK and IRE1α are type I transmembrane proteins with similar ER luminal domain structures and a cytosolic Serine/threonine kinase domain, whereas ATF6α is a type II transmembrane protein that contains a cytosolic cyclic AMP response element-binding protein (CREB)–ATF basic leucine zipper domain [ 31 , 32 , 33 , 34 ]. IRE1α, PERK, ATF6 and CREBH are ultimately responsible for the activation of a set of transcription factors (TF), including spliced X-box binding protein 1 (XBP1s), activating transcription factor 4 (ATF4), CCAAT enhancer-binding protein (C/EBP) homologous protein (CHOP), nuclear factor κB (NF-κB) and activator protein 1 (AP-1), through a complicated and nonparallel process [ 35 , 36 , 37 , 38 , 39 ].…”
Section: Er Stress and Uprmentioning
confidence: 99%